Recent progress on HYSPEC, and its polarization analysis capabilities - Winn Barry; Filges Uwe; Garlea V. Ovidiu; Graves-Brook Melissa; Hagen Mark; Jiang Chenyang; Kenzelmann Michel; Passell Larry; Shapiro Stephen M.; Tong Xin; Zaliznyak Igor (EPJ Web of Conferences, 2015)
HYSPEC is a high-intensity, direct-geometry time-of-flight spectrometer at the Spallation Neutron Source, optimized for measurement of excitations in small single-crystal specimens with optional polarization analysis capabilities. The incident neutron beam is monochromated using a Fermi chopper with short, straight blades, and is then vertically focused by Bragg scattering onto the sample position by either a highly oriented pyrolitic graphite (unpolarized) or a Heusler (polarized) crystal array. Neutrons are detected by a bank of 3He tubes that can be positioned over a wide range of scattering angles about the sample axis. HYSPEC entered the user program in February 2013 for unpolarized experiments, and is already experiencing a vibrant research program. Polarization analysis will be accomplished by using the Heusler crystal array to polarize the incident beam, and either a 3He spin filter or a supermirror wide-angle polarization analyser to analyse the scattered beam. The 3He spin filter employs the spin-exchange optical pumping technique. A 60∘ wide angle 3He cell that matches the detector coverage will be used for polarization analysis. The polarized gas in the post-sample wide angle cell is designed to be periodically and automatically refreshed with an adjustable pressure of polarized gas, optically pumped in a separate cell and then transferred to the wide angle cell. The supermirror analyser has 960 supermirror polarizers distributed over 60∘, and has been characterized at the Swiss Spallation Neutron Source. The current status of the instrument and the development of its polarization analysis capabilities are presented.